Geothermal reservoir characterisation of Devonian carbonates in North Rhine-Westphalia (W. Germany): Mineralogy- and depofacies-related extrapolation of petrophysical parameters. (December 2022) - Lippert, Kevin; Ahrens, Benedikt; Nehler, Mathias; Balcewicz, Martin; Mueller, Mathias; Bracke, Rolf; Immenhauser, Adrian
Abstract: Across Germany, coal-fired power plants will be shut down not later than 2038. In the Rhine-Ruhr area of western Germany, their waste heat is the main supply for one of Europe's largest district heating networks. Because of the projected shutdown of coal-fired power plants, sustainable alternatives must be implemented. This paper evaluates the hydrothermal potential of Devonian carbonates. A depofacies and mineralogy model is proposed and discussed. Tentative conclusions are drawn based on petrophysical laboratory tests. Extrapolating the thermal and hydraulic rock properties into geothermal reservoir depths offers constraints for associated reservoir simulations. This task applies existing and derived extrapolation equations taking local pressure and temperature gradients into consideration. The change from a non-linear to a linear development at the critical crack-closure pressure provides evidence regarding the petrophysical in-situ reservoir conditions. Results show a positive effect of increased dolomite volumes on reservoir properties. The spatial distribution of fracture networks significantly affects the geothermal reservoir potential, whereas the impact of regionally distributed depofacies variations is moderate. The critical crack-closure pressure equals 40 MPa for limestones and 60 MPa for dolomitic limestones, as well as dolostones, representing depths of approx. 3.6 and 5.4 km, respectively. At depths of 6 km, non-linear and linear extrapolation principles must be applied accordingly. At that depth, the thermal conductivity decreases by 14 to 20% compared to the outcrop values, depending on the sample category. The equivalent decrease in porosity amounts to one to two orders of magnitude. The permeability decrease equals three to four orders of magnitude. The petrophysical values of outcrop samples discussed here plot, within the error range, in the same domain as those of the Malm carbonates in the Munich area. Results are considered encouraging for those concerned with the sustainable transition of the district heating network in the Rhine-Ruhr area. Side-strands of regionally important fault systems, often characterised by hydrothermal dolomitisation, combine tectonic and petrophysical aspects that are advantageous and highly relevant for hydrothermal operations. Highlights: Devonian Massenkalk carbonates exhibit promising geothermal reservoir properties. Fracture peculiarities are crucial for the hydraulic reservoir potential. Dolomitisation further enhances the reservoir potential of Massenkalk carbonates. Pressure effect on hydraulic properties is crucial for extrapolation models.